Pelaksanaan Konseling Behaviour dengan Teknik Self Control Untuk Mengatasi Kecanduan Game Online Peserta didik di SMK Muhammadiyah Karanganyarkabupaten Pekalongan - Kurniasih, Pangestuti (Cakrawala: Jurnal Pendidikan, 2022)
This type of research is field action research. Sources of informants consist of 25 people. divided into 2 sources, primary data 5 students who are addicted to online games and secondary 20 students who are not addicted to games, parents, principals. Data collection techniques carried out by researchers by means of participant observation, and unstructured interviews. Based on the results of research conducted, it can be concluded that students who are addicted to online games due to lack of parental attention initially (100%) and have changed (60%), the initial friendship factor (100%) and has changed (80%), and stress relief. initially (100%) and has changed (80%). the application of CBT counseling is carried out in 2 cycles containing material about bad things that will arise from playing online games such as being able to make students accustomed to saying dirty words, lying to parents, being lazy to do schoolwork